1986
DOI: 10.1144/gsl.eng.1986.003.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water on engineering properties of weathered rocks

Abstract: The influence of groundwater on the engineering properties of rocks is well known. Because of its importance, rock mass classification methods include groundwater as one of the main classification parameters. Perhaps the best indication of the influence of groundwater on rock mass properties comes from the application of geophysical resistivity and seismic refraction techniques to investigate groundwater. When ground conditions change from an unsaturated to a saturated state, resistivity and velocity of the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…How the sandstone was fractured, when subjected to external loading, has been studied (Zhang et al 1990;Sangha et al 1974;Menenaez et al 1996). In summary, wetted sandstones may become softer and weaker than dry sandstones (Bell 1978;Turk and Dearman 1986;Dobereiner and De Freitas 1986;Dyke and Dobereiner 1991). The degree of wetting softening can be related to porosity (Turk and Dearman 1986) and matrix content or mineral composition (Hawkins and McConnell 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the sandstone was fractured, when subjected to external loading, has been studied (Zhang et al 1990;Sangha et al 1974;Menenaez et al 1996). In summary, wetted sandstones may become softer and weaker than dry sandstones (Bell 1978;Turk and Dearman 1986;Dobereiner and De Freitas 1986;Dyke and Dobereiner 1991). The degree of wetting softening can be related to porosity (Turk and Dearman 1986) and matrix content or mineral composition (Hawkins and McConnell 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, wetted sandstones may become softer and weaker than dry sandstones (Bell 1978;Turk and Dearman 1986;Dobereiner and De Freitas 1986;Dyke and Dobereiner 1991). The degree of wetting softening can be related to porosity (Turk and Dearman 1986) and matrix content or mineral composition (Hawkins and McConnell 1992). Wetting weakening is of concern when assessing the stability of a dry rock slope that can be wetted due to heavy rainfall, or when predicting the crown settlement of an excavating tunnel that can be wetted by seeping water inside the tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while [20] found that the effect of moisture content is not pronounced through studying the ratio of the compressive strength of oven-dried to the compressive strength of air dried of five types of rocks namely: marble, limestone, granite, sandstone, and slate. The authors of [32] found that the compressive strength for saturated specimens of massive epidiorite and schistose epidiorite decreased by (81 -86)% and (85 -90)% of dry compressive strength; respectively. Furthermore, in [33] it is stated that the moisture content may decrease the compressive strength of sandstones by 40% and shales by 60 %.…”
Section: Effect Of Moisture Contentthementioning
confidence: 99%
“…The slake durability index (Sd) was devised by Franklin and Chandra (1972) to assess the durability or weatherability of clastic sedimentary rocks such as mudstone, claystone and shale, particularly useful for rocks with significant clay content (Moon and Beattie 1995, Gokceoglu 1997, Koncagul and Santi 1999, Gokceoglu et al 2000, Sadisun et al 2005, but there are some limitations and weaknesses associated with this method (Erguler and Ulusay 2009). The other weathering indices are dry density (e.g.Banfield 1985, Turk and Dearman 1985, Eggleton et al 1987, Irfan 1996, Ceryan 2008, Ceryan 2011, Schmidt hammer rebound value (e.g. Irfan and Dearman 1978a, Martin and Hencher 1982, İrfan and Powell 1985, Lee 1987, Guolin and Yushan 1990, Zhao et al 1993, GCO 1994, Gokceoglu 1997, Ceryan et al 2008a, Basu et al 2009, the elastic wave velocity (e.g.…”
Section: ( )mentioning
confidence: 99%
“…Irfan and Dearman 1978a, Martin and Hencher 1982, İrfan and Powell 1985, Lee 1987, Guolin and Yushan 1990, Zhao et al 1993, GCO 1994, Gokceoglu 1997, Ceryan et al 2008a, Basu et al 2009, the elastic wave velocity (e.g. Illev 1967, Kılıc 1995, Dearman and Irfan 1978, Krank and Watters 1983, Turk and Dearman 1985, Lee 1987, Dearman et al 1987, Dobereiner et al 1993, Weiss et al 2002, Ceryan and Sen 2003, Kocbay 2003, Gurocak and Kilic 2005, Arikan et al 2007,Ceryan et al 2008a, 2008b, Basu et al 2009, Korkmaz and Ceryan 2011, porosity, effective porosity and void ratio (e.g. Ondera et al 1974, İrfan and Dearman 1978b, Türk ve Dearman 1985, Paşamehmetoğlu et al1981, Lumb 1983, Lee, 1987, Esaki and Jiang 1999, Gupta and Rao 2001, Ceryan et al 2008a, Gokceoglu et al 2009, Rigopoulos et al 2010, Marques et al 2010.…”
Section: ( )mentioning
confidence: 99%